2015
DOI: 10.1177/1069397115595374
|View full text |Cite
|
Sign up to set email alerts
|

Center-Periphery Dissonance as a Possible Factor of the Revolutionary Wave of 2013-2014

Abstract: Jack Goldstone proposes three predictors for acute social and political destabilization during the revolutionary wave of 2013-2014: (a) an intermediate level of per capita GDP, (b) a high level of corruption, and (c) a transitional type of political regime. After testing this theory on a broader sample, this study suggests and finds support for another predictor—“center-periphery dissonance” for the destabilization of the 2013-2014 wave. The emergence of this factor is common in the process of modernization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…Our empirical tests using GDP per capita data confirm the existence of such an inverted U-shaped relationship (Korotayev, Issaev, Vasiliev, 2015;Korotayev, Issaev, Zinkina, 2015;Korotayev, Bilyuga, Shishkina, 2016, 2017a, 2017b Chapter 2; Korotayev, Vaskin, Bilyuga, 2017). In our previous article (Korotayev, Vaskin, Bilyuga, 2017), we show that this curvilinear relationship has quite a different character for different indices of sociopolitical destabilization.…”
Section: Introductionmentioning
confidence: 64%
“…Our empirical tests using GDP per capita data confirm the existence of such an inverted U-shaped relationship (Korotayev, Issaev, Vasiliev, 2015;Korotayev, Issaev, Zinkina, 2015;Korotayev, Bilyuga, Shishkina, 2016, 2017a, 2017b Chapter 2; Korotayev, Vaskin, Bilyuga, 2017). In our previous article (Korotayev, Vaskin, Bilyuga, 2017), we show that this curvilinear relationship has quite a different character for different indices of sociopolitical destabilization.…”
Section: Introductionmentioning
confidence: 64%
“…As a result, a negative correlation between per capita income and the risk of sociopolitical destabilization characterizes higher values of per capita income while a positive correlation is found for lower income values (Huntington 1968: 39-50;Olson 1963). Previous empirical tests with per capita GDP data have supported the presence of this inverted U-shaped relationship (Korotayev, Bilyuga, and Shishkina 2016Korotayev, Issaev, and Vasiliev 2015;Korotayev, Issaev, and Zinkina 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Their research that has focused on the quantitative and qualitative analysis of the Arab Spring events has demonstrated in various ways (including the application of formal mathematical models) that inconsistently authoritarian regimes turned to be the most unstable; what is more in the multiple regression analyses performed by these authors the intermediate type of the political regime has consistently turned out to be one of the strongest destabilization predictors Grinin, Issaev, and Korotayev 2015;Malkov et al 2013;Tsirel 2012a and2012b). In addition, they have demonstrated that the intermediate type of political regime was a significant predictor of political destabilization during the revolutionary wave of 2013-2014 (Korotayev, Issaev, and Zinkina 2015;Korotayev, Issaev, and Vasiliev 2015). tendency toward the replacement of intermediate regimes by democracies.…”
Section: Introductionmentioning
confidence: 99%
“…Наш интерес к связи между событиями «арабской весны» и волной дестабилизации в разных странах Восточной Европы обусловлен также и тем, что, как правило, исследователи, изучающие протестные движения, революции, антиправительственные демонстрации и другие формы социально-политической дестабилизации, объясняют возникновение подобных событий внутренними процессами, протекающими в этих странах, не учитывая дестабилизирующий потенциал «арабской весны». Чаще всего в качестве переменных, объясняющих возникновение явлений социально-политической дестабилизации, выступают показатели, отражающие социально-экономический, технологический или политический уровень развития региона, например, значение средних подушевых доходов (Olson, 1963;Huntington, 1968;Korotayev, Issaev, Zinkina, 2015;Коротаев, Билюга, Шишкина, 2017b;Коротаев, Васькин, Билюга, 2017), уровень неравенства в cтране (Sigelman, Simpson, 1977;, уровень безработицы (Barber, 2003;Beissinger, Jamal, Mazur, 2015;Jones, Rodgers, 2011;Gil-Alana, 2003;Коротаев, Хохлова, Цирель, 2018), этнолингвистическая фракционализация (Montalvo, Reynal-Querol, 2002; Малков и др., 2013), концентрация населения в большом городе/столице (DeNardo, 2014;Dowe, 2001;Tilly, 2003;, доля молодежи в общей численности населения (Goldstone, 2011(Goldstone, , 2017Urdal, 2004;Коротаев, Зинькина, 2011;Коротаев, Малков, 2014; Романов и др., 2018), уровень образования (Brockhoff et al, 2015;Elbakidze, Jih, 2015;Korotayev, Bilyuga, Shishkina, 2018;Коротаев, Билюга, Шишкина, 2017a;Замятнина, 2017; Васькин и др., 2018), тип режима (Goldstone et al, 2010;Beehner, 2018), а также природные (Малков и др., 2017; Коротаев, Гринин, Исаев и др., 2017), географические (Соболев, 2013) и даже социально-психологические факторы -связанные с чувством фрустрации и относительной депривации у населения (Davies, 1962;Gurr, 1970;Di Stefano et al, 2017;…”
Section: литератураunclassified
“…Однако в Бангкоке лидирующая партия обладала лишь 30% голосов. Таким образом, оказалось, что население столицы поддерживает оппозиционную партию (что было подтверждено и на выборах мэра в 2013 году), в результате чего Бангкок стал эпицентром протестов в 2013 году, а в 2014м власть в Бангкоке была взята военными (Korotayev, Issaev, Zinkina, 2015). После прихода к власти военных политические силы оказались лишены возможности выражать свой протест легальным путем, что спровоцировало рост числа террористических атак.…”
Section: нетипичные случаи дестабилизации: кейс украиныunclassified